NEDD4L in human tumors: regulatory mechanisms and dual effects on anti-tumor and pro-tumor - Zhang, Meng; Zhang, Zhenyong; Tian, Xin; Zhang, Enchong; Wang, Yichun; Tang, Jun; Zhao, Jianzhu (Frontiers in Pharmacology, 2023)
Tumorigenesis and tumor development are closely related to the abnormal regulation of ubiquitination. Neural precursor cell expressed developmentally downregulated 4-like (NEDD4L), an E3 ubiquitin ligase critical to the ubiquitination process, plays key roles in the regulation of cancer stem cells, as well as tumor cell functions, including cell proliferation, apoptosis, cell cycle regulation, migration, invasion, epithelial–mesenchymal transition (EMT), and tumor drug resistance, by controlling subsequent protein degradation through ubiquitination. NEDD4L primarily functions as a tumor suppressor in several tumors but also plays an oncogenic role in certain tumors. In this review, we comprehensively summarize the relevant signaling pathways of NEDD4L in tumors, the regulatory mechanisms of its upstream regulatory molecules and downstream substrates, and the resulting functional alterations. Overall, therapeutic strategies targeting NEDD4L to treat cancer may be feasible.